Places et rôles des passeurs dans les Lieux d’éducation associés à l’Institut français de l’éducation - Aurore Promonet; Michèle Prieur (Recherches en Éducation)
The study is part of a collaborative research network: the Lieux d'éducation associés de l'Institut français de l'éducation de l'École normale supérieure de Lyon (LéA-IFÉ). A LéA is linked to education and/or training issues and brings together, for three years, actors from the world of research and the world of education around a co-constructed research project. We question the places and roles of the different actors involved in a Lea. Based on the functions assigned to them by their institutions, we study the roles assumed by each and potentially distributed within the research. In the first part of the article, we deal with the question based on a case study from a particular LéA (LéA TEC: written traces practiced from school to middle school in the Land of Lorraine). In the second part, we present the analysis of a specific role in the context of collaborative research: the role of knowledge broker. The issue is addressed at the level of the LeA-IFÉ network.